Loss to follow-up and associated maternal factors among HIV-exposed infants at the Mbarara Regional Referral Hospital, Uganda: a retrospective study - Ankunda, Rogers; Cumber, Samuel N.; Atuhaire, Catherine; Kabanda, Taseera; Nkfusai, Claude N.; Wirsiy, Frankline S.; Turyakira, Eleanor (BMC Infectious Diseases, 2020)
Loss to follow-up (LTFU) deprives HIV-exposed infants the lifesaving care required and results in exposing HIV free infants to virus requisition risk. We aimed to determine the rate of LTFU, postnatal mother-tochild HIV-transmission (MTCT) and to identify maternal factors associated with LTFU among HIV-exposed infants enrolled at Mbarara Regional Referral Hospital PMTCT clinic. Methods: Study participants were infants born to HIV-positive mothers enrolled in the PMTCT clinic for HIV care at Mbarara Regional Referral Hospital. While access database in the Early Infant Diagnosis (EID) clinic provided data on infants, the open medical record system database at the ISS clinic provided that for mothers. Infants were classified as LTFU if they had not completed their follow-up schedule by 18 months of age. At 18 months, an infant is expected to receive a rapid diagnostic test before being discharged from the PMTCT clinic. Postnatal MTCT of HIV was calculated as a proportion of infants followed and tested from birth to 18 months of age. Logistic regression was used to determine possible associations between mothers’ characteristics and LTFU. In-depth interviews of mothers of LTFU infants and health workers who attend to the HIV-exposed infants were carried out to identify factors not captured in the electronic database. Results: Out of 1624 infants enrolled at the clinic, 533 (33%) were dropped for lack of mother’s clinic identification number, 18 (1.1%) were either dead or transferred out. Out of 1073 infants analysed, 515 (48%) were LTFU by 18 months of age while out of the 558 who completed their follow-up schedule, 20 (3.6%) tested positive for HIV. Young age of mother, far distance to hospital and non-use of family planning were identified as outstanding factors responsible for LTFU. In addition, in-depth interviews revealed facility-level factors such as “waiting time” which would not be found in routine client databases.
Keywords: HIV-exposed infants; Loss to follow up; Post-natal mother to child transmission